SOME SPECIFIC EPIDEMIOLOGICAL AND CLINICO-MORPHOLOGICAL FEATURES OF MALE BREAST CANCER - Sovhyria, S.N.; Vynnyk, N.I.; Filenko, B.M.; Serbin, S.I.; Agashkov, Ye.O. (World of Medicine and Biology, 2018)
The paper presents current data on the features of male breast cancer (MBC) morbidity and mortality. The analysis of rates in Poltava region has been carried out. It has been revealed, that the level of MBC morbidity and mortality is similar to the national rates and conforms to the global tendencies. The need for significant improvement of diagnosis by active implementation of the advanced pathomorphological methods has been substantiated. The paper is also highlights the necessity for physicians of different specialization to be more aware about oncological diseases with rare localization, requiring more oncological alertness.